(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: Diabetes is a chronic disease with a high risk of disability and death. In addition to physical complications, some psychological problems especially depression and loss of psychological capital are also common in people with diabetes. This study aimed to investigate the effectiveness of Compassion-Focused Therapy (CFT) training on psychological capital and depression in female adolescents with type 1 diabetes. Methods: The research method was quasi-experimental with pretest-posttest and follow-up. The statistical population of the study was all adolescents aged 16-14 years with type 1 diabetes in Sanandaj City. The statistical sample consisted of 30 adolescents with type 1 diabetes who were purposefully selected and randomly divided into experimental (n=15) and control (n=15) groups. The PCQ-24 scale was used to collect data to measure psychological capital and the BDI-II scale was used to measure depression. The experimental group received 90 minutes of skill training based on CFT in eight sessions, but the control group did not receive any intervention. Data were analyzed by repeated measure in SPSS software v. 25. Results: The results showed that skill training based on CFT was effective on psychological capital and depression in adolescent girls with type 1 diabetes in the post-test phase (Pvalue<0.05), and had a lasting effect (Pvalue<0.05). Conclusions: The results showed that Skill Training Based on CFT is effective on psychological capital and depression, so it is recommended that clinical psychologists use this training to increase the psychological health of patients with type 1 diabetes. Keywords: Skill Training, Compassion-Focused Therapy, Psychological Capital, Depression, Diabetes type 1